Correction: Research on auditory and olfactory regulation methods for abnormal driver emotions based on EEG signals - Tang, Bangbei; Li, Yan; Wu, Yingzhang; Li, Yilun; Yue, Qizong (Frontiers in human neuroscience, 2025)
[This corrects the article DOI: 10.3389/fnhum.2025.1615346.].